Utilization of Alum And Lemon Peel (Citrus Limon L.) as A Natural Ingredient For Making Deodorant Spray - Afifah Sabri, Nur Rahmayanti; Mustiqawati, Evi; Nurwanti, Ratih (International Journal of Multidisciplinary Learners, 2025)
Excessive sweating can cause problems for some people, such as unpleasant body odor. Spray deodorant is one way to treat body odor. Lemon peel is one of the herbal ingredients that can be used to make deodorant spray. Citric acid, which has antibacterial properties, is found in lemon peels. Ingredients such as potassium aluminum sulfate, which functions as an antiperspirant, can also be added. The purpose of this study was to determine the physical evaluation test of deodorant spray formulations with lemon peel extract (Citrus limon L.) in various concentrations and also to determine the formulations with different concentrations. This study is a type of qualitative research that uses experimental methods. The results of the study showed that deodorant preparations based on lemon peel extract (Citrus limon L.) from three concentrations carried out, namely 1%, 3% and 5%, showed that the three formulations were safe and good to use as deodorant sprays. The results of the physical evaluation test of the preparation include organoleptic test, homogeneity test, pH test, spray pattern test, dry time test and irritation test for the three formulations have met the criteria and requirements that have been set. This research makes an important contribution to the development of beauty products such as natural-based deodorants that are environmentally friendly and safe for the skin. With such positive results, lemon peel extract can be a potential natural ingredient option in the cosmetic and personal care industry.